Obstacles in the Management of Certification of Mosque Endowment Land in Perbaungan District (Implementation of Law Number 41 of 2004 Concerning Endowments) - Damanik, Hilmiyah; Yamamah, Ansyari; Syahmedi, Ramadhan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Waqf land certification in Indonesia has been governed by various regulations for decades, serving as essential authentic evidence for ensuring legal certainty of waqf land. However, data from the Perbaungan District Religious Affairs Office (KUA) in 2022 reveals that out of 88 mosque waqf lands, only 43 have been certified, while 45 remain uncertified. This situation arises due to numerous obstacles in the certification process, hindering the effective implementation of Law Number 41 of 2004 concerning Waqf. This empirical juridical study investigates the procedures and challenges in certifying mosque waqf land under the mentioned law. The study draws on primary and secondary data collected through observations, interviews, and documentation, and the data is analyzed using qualitative descriptive methods. The findings indicate that: 1) In Islamic law, waqf land certification is encouraged by the recommendation for documentation in muamalah as outlined in QS Al-Baqarah verse 282. The process and procedures are further regulated by Indonesian positive law. 2) Key obstacles include a lack of information and outreach, inadequate professionalism of waqf nazhir, administrative complexity, costs, and low public legal awareness.